2019
DOI: 10.47102/annals-acadmedsg.v48n7p224
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Ventilation in Children with Paediatric Acute Respiratory Distress Syndrome

Abstract: Introduction: Evidence supporting non-invasive ventilation (NIV) in paediatric acute respiratory distress syndrome (PARDS) remains sparse. We aimed to describe characteristics of patients with PARDS supported with NIV and risk factors for NIV failure. Materials and Methods: This is a multicentre retrospective study. Only patients supported on NIV with PARDS were included. Data on epidemiology and clinical outcomes were collected. Primary outcome was NIV failure which was defined as escalation to invasive mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Severe hypoxemia has been consistently reported as a risk factor for NIV failure (10,11,13,23). The risk of NIV failure associated with nonpulmonary organ dysfunction is also consistent with previous studies that reported higher NIV failure rates in the presence of sepsis (10,12,23,24), vasoactive agents (25), or higher PRISM scores (10,12,23). Immunosuppression was associated with both NIV use and NIV failure in this study.…”
Section: What This Study Means?supporting
confidence: 91%
“…Severe hypoxemia has been consistently reported as a risk factor for NIV failure (10,11,13,23). The risk of NIV failure associated with nonpulmonary organ dysfunction is also consistent with previous studies that reported higher NIV failure rates in the presence of sepsis (10,12,23,24), vasoactive agents (25), or higher PRISM scores (10,12,23). Immunosuppression was associated with both NIV use and NIV failure in this study.…”
Section: What This Study Means?supporting
confidence: 91%
“…Die nichtinvasive Beatmung zu Behandlung der ARI hat ihren festen Stellenwert in der Behandlung von Säuglingen und Kinder auf der pädiatrischen Intensivstation. Die Evidenz zum Nutzen der NIV kommt u. a. aus kleineren randomisierten Studien 499 500 501 502 503 504 505 506 507 508 , Cross-over-Studien 509 510 511 512 , prospektiven 90 94 101 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 und retrospektiven Kohortenstudien 91 93 95 97 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 . Trotz der vielen Studien ist aufgrund der meist kleinen Fallzahlen und Heterogenität der untersuchten Kohorten eine Überlegenheit von NIV im Vergleich zu Standardtherapie für viele Indikationen im Kindesalter außerhalb der Neugeborenen Periode unzureichend belegt.…”
Section: Ari Bei Kindern Und Jugendlichenunclassified
“…The literature search identified 6,336 studies, 187 were selected for full-text review, and 14 underwent data extraction (36–50) ( Supplemental Fig. S1 , http://links.lww.com/PCC/C300).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the use of NIV in PARDS is based mostly on observational studies and two randomized controlled trials (RCTs) ( Table 1 ) (3–8, 10, 18, 28, 29, 36, 37, 43, 46, 48–50). Many of these studies include a heterogeneous pediatric population from at risk to severe PARDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation